2021
DOI: 10.3389/fpsyg.2021.702408
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Indigenous Personality and Parenting Style to Life Satisfaction Development in Chinese Adolescents

Abstract: The present three-wave longitudinal study examined the contributions of indigenous personality traits and parenting style to life satisfaction in Chinese adolescents. Seven hundred and ten junior high school students (Mage = 11.39, SDage = 0.53; 53.2% girls) were administered self-report measures of personality, parenting styles, and life satisfaction in Grade 6. Data on life satisfaction were collected again in Grades 7 and 8, respectively. Latent growth model analyses indicated that life satisfaction decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 91 publications
(177 reference statements)
0
6
0
Order By: Relevance
“…In contrast, the mental health of adolescents is negatively associated with parental rejection [48]. Meanwhile, some studies are focused on how different parenting styles of fathers and mothers affect children's life satisfaction [49][50][51]. Abubakar et al [51] reported that the authoritative parenting style of fathers rather than mothers positively predicts the life satisfaction of adolescents.…”
Section: The Mediating Role Of Life Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the mental health of adolescents is negatively associated with parental rejection [48]. Meanwhile, some studies are focused on how different parenting styles of fathers and mothers affect children's life satisfaction [49][50][51]. Abubakar et al [51] reported that the authoritative parenting style of fathers rather than mothers positively predicts the life satisfaction of adolescents.…”
Section: The Mediating Role Of Life Satisfactionmentioning
confidence: 99%
“…Meanwhile, recent studies have shown that parenting styles are closely related to life satisfaction [ 16 , 17 ]. The way parents educate their children can significantly predict their life satisfaction [ 18 ]. Moreover, life satisfaction has been frequently investigated as a mediating factor [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While comprehensive meta-studies report statistically significant associations between extraversion and satisfaction with correlations between 0.25 and 0.35 (Heller et al, 2004;Steel et al, 2008), others point out that many included studies suffer the problem of rather special samples, such as only from western nations or with small sizes. To give some examples, Jovanović (2019) reports a correlation of 0.26 for 500 US high-school students, other student samples, also from different cultural backgrounds, report similar effect sizes (Li, 2021). Another study used a sample of 158 Amazon's Mechanical Turk Service and reports a correlation of 0.41 (Smith & Konik, 2022).…”
Section: Previous Research Findingsmentioning
confidence: 99%
“…Overprotective parenting refers to parents' excessive attention and control over their children's daily behavior. The overprotection is detrimental to individual's independence (Segrin et al, 2012;Li, 2021).…”
Section: Parenting Styles and Emotion Regulationmentioning
confidence: 99%